Pan-Genomic Study of Mycobacterium tuberculosis Reflecting the Primary/Secondary Genes, Generality/Individuality, and the Interconversion Through Copy Number Variations - Yang, Tingting; Zhong, Jun; Zhang, Ju; Li, Cuidan; Yu, Xia; Xiao, Jingfa; Jia, Xinmiao; Ding, Nan; Ma, Guannan; Wang, Guirong; Yue, Liya; Liang, Qian; et al. (Frontiers in Microbiology, 2018)
In the past two years, tuberculosis (TB) has surpassed HIV as the leading infectious disease killer worldwide. The main pathogen, Mycobacterium tuberculosis (Mtb), contains ~4000 genes that account for ~90% of the genome. However, it is still unclear which of these genes are primary/secondary, which are responsible for generality/individuality, and which interconvert during evolution. We utilized a pan-genomic analysis of 36 Mtb genomes to address these questions. We identified 3,679 Mtb core (i.e., primary) genes, and determined their phenotypic generality (e.g., virulence, slow growth, dormancy). There were 1,122 dispensable and 964 strain-specific secondary genes; these reflect partially shared and lineage-/strain-specific individualities. Compared with Mycobacterium bovis (Mbo), Mtb possesses 48 specific single core genes that partially reflect the differences between Mtb and Mbo individuality. We also observed five L2 lineage-specific genes that might be related to the increased virulence of the L2 lineage. Notably, we discovered 28 Mtb “Super Core Genes” (SCGs: more than a copy in at least 90% strains), which might be of increased importance, and reflected the “super phenotype generality”. Most SCGs encode PE/PPE, virulence factors, antigens, and transposases, and have been verified as playing crucial roles in Mtb pathogenicity. Further investigation of the 28 SCGs demonstrated the interconversion among SCGs, single-copy core, dispensable, and strain-specific genes through CNVs during evolution. Also, different mutations on different copies highlight the delicate adaptive-evolution regulation amongst Mtb lineages. This reflects that the importance of genes varied through CNVs, which might be driven by selective pressure from environment/host-adaptation.